2018
DOI: 10.1302/2046-3758.72.bjr-2017-0337.r1
|View full text |Cite
|
Sign up to set email alerts
|

A pilot hole does not reduce the strains or risk of fracture to the lateral cortex during and following a medial opening wedge high tibial osteotomy in cadaveric specimens

Abstract: AimIt has been suggested that the use of a pilot-hole may reduce the risk of fracture to the lateral cortex. Therefore the purpose of this study was to determine the effect of a pilot hole on the strains and occurrence of fractures at the lateral cortex during the opening of a high tibial osteotomy (HTO) and post-surgery loading.Materials and MethodsA total of 14 cadaveric tibias were randomized to either a pilot hole (n = 7) or a no-hole (n = 7) condition. Lateral cortex strains were measured while the osteot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Their results confirm that, for tibial varus correction osteotomies < 5°, drilling a hole at the end of the osteotomy reduces stresses in the lateral hinge and increases the critical angle before failure of the hinge but only for corrections inferior to 5°. Indeed, for osteotomies superior to 9 mm of opening in cadaveric specimens, Bujnowski et al [4] recently demonstrated that a pilot hole showed no significant decrease in the strains experienced at the lateral cortex, nor did it reduce the risk of fracture of the lateral tibial hinge. According to Diffo Kaze et al [6], the ductility of the cortical bone is the decisive parameter for the critical angle of opening, defined as the angle from which the tibial hinge breaks.…”
Section: Discussionmentioning
confidence: 99%
“…Their results confirm that, for tibial varus correction osteotomies < 5°, drilling a hole at the end of the osteotomy reduces stresses in the lateral hinge and increases the critical angle before failure of the hinge but only for corrections inferior to 5°. Indeed, for osteotomies superior to 9 mm of opening in cadaveric specimens, Bujnowski et al [4] recently demonstrated that a pilot hole showed no significant decrease in the strains experienced at the lateral cortex, nor did it reduce the risk of fracture of the lateral tibial hinge. According to Diffo Kaze et al [6], the ductility of the cortical bone is the decisive parameter for the critical angle of opening, defined as the angle from which the tibial hinge breaks.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the difference of having a drill hole or not at the end of a horizontal osteotomy was investigated, and the effect on reducing the risk of lateral cortex fracture was not significant, especially for older patients [64]. A cadaveric experiment produces similar conclusions that there was no significant difference in the strains on the lateral cortex during OWHTO between the pilot hole and no-hole conditions [65].…”
Section: Fixation Platementioning
confidence: 99%
“…The osteotomy fixation plate experiences greater stresses and strains in the presence of fracture increasing the possibility of fatigue failure especially in delayed union 10. The effect of an apical drill hole in opening wedge HTO has been investigated previously in an experimental biomechanical model, though Bujnowski et al18 concluded no benefit in terms of cortical strain reduction or risk of lateral fracture in a cadaveric study of 14 paired specimens. Only one diameter of the drill hole was investigated and the cortical strain was measured at a single location using a single strain gauge.…”
mentioning
confidence: 99%